APPROACHES TO ENHANCING MONETARY POLICY METHODS AND TOOLS IN UZBEKISTAN, INFORMED BY INTERNATIONAL BEST PRACTICES - Yuldasheva Shokhsanam Dilmuradovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation. This article explores the current monetary policy framework in Uzbekistan and identifies ways to enhance its effectiveness by drawing on international best practices. It examines the challenges faced by Uzbekistan’s central bank in implementing monetary policy tools and suggests that adopting strategies such as inflation targeting, flexible exchange rate policies, and improved communication could strengthen policy outcomes. The research highlights the need for greater central bank autonomy, better financial market development, and enhanced analytical capacity to support more effective monetary policy. Ultimately, the article proposes a roadmap for improving Uzbekistan’s monetary policy framework to achieve greater price stability and sustainable economic growth.